2016
DOI: 10.5301/jva.5000595
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Ultrasound for the Prediction of Vascular Events Associated with Arteriovenous Fistulas in Hemodialysis Patients

Abstract: US evaluation of AVFs in HD patients is a simple method to predict the risks of thrombosis and fistula dysfunction. Qa, ferritin, transferrin saturation, and warfarin use might be associated with VEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…However, the RIs of the arteries had similar changing trends, inferring that the RI is not a sensitive marker for identifying the function of AVFs. This result was different from those of other studies, which suggested that the RI cut-off was 0.56 for fistula intervention 20 or 0.63 for early fistula failure. 18 The differences in the enrolled patients, AVF failure definitions, and observed endpoints might be attributed to these varying results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the RIs of the arteries had similar changing trends, inferring that the RI is not a sensitive marker for identifying the function of AVFs. This result was different from those of other studies, which suggested that the RI cut-off was 0.56 for fistula intervention 20 or 0.63 for early fistula failure. 18 The differences in the enrolled patients, AVF failure definitions, and observed endpoints might be attributed to these varying results.…”
Section: Discussioncontrasting
confidence: 99%
“…The earliest time points to predict the outcome of AVFs changed from 1 day to 12 weeks after surgery. 12,14,1820,24,25…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis can be prevented by having a closer look at stenosis. An active screening strategy by systematic Doppler or Transonic ® flow rates could reduce the risk of thrombotic events of VA [27,28]. European and international guidelines recommend regular and objective monitoring of access function (ideally every month for AVG and every 3 months for AVF) [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that to reduce blood clots formation, a fistula with an outflow vein length sufficient for puncturesat least 30-35 cm is required [7]. Studies have shown that the risk of thrombosis is significantly reduced with minimum access flow in the fistula of about 580 ml/min [20]. In addition to visualizing thrombotic masses in the vessel lumen, ultrasound criteria for arteriovenous fistula thrombosis include the absence of vein compressibility and impaired blood flow phasicity during breathing [8].…”
Section: Arteriovenous Fistula Thrombosismentioning
confidence: 99%